Estudo experimental do ângulo de abertura de difusores cônicos em um microgerador eólico - SILVA, Thales Cunha e (2019)
This work aims to evaluate the influence of the opening angle of conical diffusers in a wind micro generator using low cost materials. The diffuser, or power intensifier, acts in the formation of low-pressure zones in the outlet section, promoting an effect of ―suction‖ of the air stream, increasing the speed that affects the wind turbine rotor, consequently increasing the generation of electric power. In this work, five conical diffusers with inlet diameter and fixed lengths were built, varying their opening angles, in this case, 5º, 10º, 15º, 20º and 25º. The ratio between the length of each diffuser (L/d) and its inlet diameter was 0.5. The wind tunnel used for the tests was built with low cost materials, as well as the wind generator. Electrical voltage readings were taken through the micro generator inside each diffuser. Then, velocity readings were taken through the Pitot tube inside each diffuser. From these values, the factors of speed increase and electric voltages were determined, which were later compared. It was observed that all diffusers promoted speed and voltage increase. It was also observed that for the ratio L/d used, the velocity ratios and the stress ratios increased as the opening angle increased. However, high opening angles, such as 40 °, cause speed reduction, as seen in Barbosa (2013). The results showed the influence of diffuser geometry in increasing the generation of velocities and electric voltages of up to 32%, but in different locations. The results obtained in this work are in good agreement with the works available in the literature, even though conical diffusers where less used in wind applications.